2020
DOI: 10.1002/ptr.6795
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone inhibits the proliferation and invasion of esophageal cancer cells by disrupting the AKT/GSK‐3β/Wnt signaling pathway via PTEN upregulation

Abstract: Although thymoquinone (TQ) has been reported to exert antitumor activity against various types of human cancers without evident toxicity, limited studies have reported the effects of TQ on esophageal cancer. Here, we showed that TQ induced cell cycle arrest in the G2/M phase and significantly inhibited cell proliferation and invasion. Further investigation of the potential mechanism revealed that TQ increased the levels of p53 and p21 but significantly reduced the expression of Cyclin B1, Cyclin A, and Cyclin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution. [22][23][24] Cyclin B1 played a key role in G2/M phase of cell cycle distribution. 25 Downregulation of CDK1 could induce G2/M arrest, 26 while p27 Kip1 was negatively correlated with cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution. [22][23][24] Cyclin B1 played a key role in G2/M phase of cell cycle distribution. 25 Downregulation of CDK1 could induce G2/M arrest, 26 while p27 Kip1 was negatively correlated with cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TQ displayed a hyperproliferative effect in rats and also abrogated Fe (III) nitrilotriacetic acid (Fe-NTA) induced oxidative stress [ 63 ]. TQ reduced Cyclin A, Cyclin B1, Cyclin D1 and Cyclin E [ 82 , 83 , 84 , 85 ] expression and increased levels of p21 and p53 [ 86 , 87 ]. TQ is capable of decreasing Bcl-2 and increasing cleaved caspase-3, 9, and 7, and Bax proteins, as well as modulating the expression of microRNA (miRNA) and long non-coding RNAs (lncRNA), acetylation/deacetylation of histone along with methylation/demethylation of DNA, resulting in mitochondrial apoptosis induction [ 61 , 63 , 88 , 89 ].…”
Section: Neoplasm and Its Pathogenesismentioning
confidence: 99%
“…TQ is capable of decreasing Bcl-2 and increasing cleaved caspase-3, 9, and 7, and Bax proteins, as well as modulating the expression of microRNA (miRNA) and long non-coding RNAs (lncRNA), acetylation/deacetylation of histone along with methylation/demethylation of DNA, resulting in mitochondrial apoptosis induction [ 61 , 63 , 88 , 89 ]. TQ also halts the PI3K/AKT signaling pathway by upregulating PTEN, thus interfering with GSK-3β activity, enhancing β-catenin degradation, and decreasing MMP-9 and MMP-2 levels in esophageal cancer cells (Eca109 cells) [ 83 ]. MicroRNA-34a (miR-34a) expression is vital to cancer development and metastasis [ 90 ], and its expression is reduced by TQ in human metastatic breast cancers (MBC) compared to normal breast tissues [ 91 ].…”
Section: Neoplasm and Its Pathogenesismentioning
confidence: 99%
“…According to different ways of signal transduction by Wnt protein, Wnt signal transduction can be divided into the canonical Wnt signal pathway and the non-canonical Wnt signaling pathway. Some studies have demonstrated that the Wnt signal pathway is involved in proliferation and migration of ESCC [29][30][31] . In recent years, studies have found that both the canonical and the non-canonical Wnt signal pathways are involved in the induction of EMT.…”
Section: Discussionmentioning
confidence: 99%